Environmental Enrichment Prevents Transcriptional Disturbances Induced by Alpha-Synuclein Overexpression - Wassouf, Zinah; Hentrich, Thomas; Samer, Sebastian; Rotermund, Carola; Kahle, Philipp J.; Ehrlich, Ingrid; Riess, Olaf; Casadei, Nicolas; Schulze-Hentrich, Julia M. (Frontiers in Cellular Neuroscience, 2018)
Onset and progression of neurodegenerative disorders, including synucleinopathies such as Parkinson’s disease, have been associated with various environmental factors. A highly compelling association from a therapeutic point of view has been found between a physically active lifestyle and a significantly reduced risk for Parkinson’s disease. Mimicking such conditions in animal models by promoting physical activity, social interactions, and novel surroundings yields in a so-called enriched environment known to enhance adult neurogenesis, increase synaptic plasticity, and decelerate neuronal loss. Yet, the genes that connect beneficial environmental cues to the genome and delay disease-related symptoms have remained largely unclear. To identify such mediator genes, we used a 2×2 factorial design opposing genotype and environment. Specifically, we compared wildtype to transgenic mice overexpressing human SNCA, a key gene in synucleinopathies encoding alpha-synuclein, and housed them in a standard and enriched environment from weaning to 12 months of age before profiling their hippocampal transcriptome using RNA-sequencing. Under standard environmental conditions, differentially expressed genes were overrepresented for calcium ion binding, membrane, synapse, and other Gene Ontology terms previously linked to alpha-synuclein biology. Upregulated genes were significantly enriched for genes attributed to astrocytes, microglia, and oligodendrocytes. These disturbances in gene activity were accompanied by reduced levels of several presynaptic proteins and the immediate early genes EGR1 and NURR1. Intriguingly, housing transgenic animals in the enriched environment prevented most of these perturbations in gene activity. In addition, a sustained activation specifically in transgenic animals housed in enriched conditions was observed for several immediate early genes including Egr1, Nr4a2/Nurr1, Arc, and Homer1a. These findings suggest a compensatory mechanism through an enriched environment-activated immediate early gene network that prevented most disturbances induced by alpha-synuclein overexpression. This regulatory framework might harbor attractive targets for novel therapeutic approaches that mimic beneficial environmental stimuli.